2011
DOI: 10.1523/jneurosci.2443-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Resolving TRPV1- and TNF-α-Mediated Spinal Cord Synaptic Plasticity and Inflammatory Pain with Neuroprotectin D1

Abstract: Mechanisms of inflammatory pain are not fully understood. We investigated the role of TRPV1 and TNF-α, two critical mediators for inflammatory pain, in regulating spinal cord synaptic transmission. We found in mice lacking Trpv1 the frequency but not the amplitude of spontaneous EPSCs (sEPSCs) in lamina II neurons of spinal cord slices is reduced. Further, C-fiber-induced spinal long-term potentiation (LTP) in vivo is abolished in Trpv1 knockout mice. TNF-α also increases sEPSC frequency but not amplitude in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
219
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(229 citation statements)
references
References 84 publications
8
219
2
Order By: Relevance
“…Understanding the regulation of presynaptic receptors by proinflammatory cytokines would reveal synaptic mechanisms by which glial cells alter spinal nociceptive processing. In this regard, it was recently reported that TNF-␣ increases glutamate release from presynaptic terminals via TRPV1 receptors (73). Our findings that presynaptic NMDA receptors in the primary afferent terminals are the effector receptors used by endogenous IL-1␤ to increase glutamate release from the primary afferent terminals are the first to reveal the functional coupling between presynaptic NMDA receptors and IL-1␤.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Understanding the regulation of presynaptic receptors by proinflammatory cytokines would reveal synaptic mechanisms by which glial cells alter spinal nociceptive processing. In this regard, it was recently reported that TNF-␣ increases glutamate release from presynaptic terminals via TRPV1 receptors (73). Our findings that presynaptic NMDA receptors in the primary afferent terminals are the effector receptors used by endogenous IL-1␤ to increase glutamate release from the primary afferent terminals are the first to reveal the functional coupling between presynaptic NMDA receptors and IL-1␤.…”
Section: Discussionsupporting
confidence: 58%
“…Primary (73) increases glutamate release from the central terminals of primary afferents. Added to this complexity of presynaptic regulation mechanisms is the presynaptic NMDA receptor reported recently by us and others.…”
Section: Discussionmentioning
confidence: 99%
“…TNF␣ and IL-6 were significantly correlated with evoked pain measures in the PTSD group, whereas there was no correlation between proinflammatory cytokine concentrations and any pain measure in the CC group. CNS release of TNF␣ can lower pain thresholds by modulating the number of neuronal membrane ion channels and their functional activity (Choi et al, 2010), which can result in hyperexcitable pain circuits within dorsal horn (Reeve et al, 2000;Park et al, 2011;Kawasaki et al, 2008). TNF␣ binding to the microglial TNF␣ receptor (TNF␣-R) stimulates p38 mitogen-activated protein kinase (P38 MAPK) phosphorylation and activation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to TNF␣, both inflammatory and neuropathic pain models have shown that IL-1␤ is synthesized and secreted from astrocytes, neurons, and microglia. IL-1␤ enhances activity in the lamina II of the dorsal horn by multiple mechanisms (Reeve et al, 2000;Park et al, 2011;Kawasaki et al, 2008) and is known to amplify pain signaling. Increased IL-1␤ secretion in the PTSD-group may enhance pain nociception, which is a conclusion supported in our study by the following: 1) increases in spontaneously reported pain intensity and unpleasantness and 2) the increased evoked pain measure of temporal summation.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-cell patchclamp recordings were performed at room temperature to measure inward currents (voltage clamp, at -60 mV holding potential) and action potentials (current clamp) in small-sized DRG neurons, using Axopatch-200B amplifier (49). Whole-cell patch-clamp recordings were also conducted in lamina II neurons in spinal cord slices (30) to measure sEPSC in a voltage clamp mode (-70 mV).…”
Section: Patch-clamp Recordings In Drg Neurons and Spinal Cord Slicesmentioning
confidence: 99%